Carboxylative cyclization of propargylic alcohols with carbon dioxide: A facile and Green route to α-methylene cyclic carbonates. Issue 38 (May 2020) - Li, Mingli; Abdolmohammadi, Shahrzad; Hoseininezhad-Namin, Mir Saleh; Behmagham, Farnaz; Vessally, Esmail
Highlights: Significant advances and developments in the synthesis of α-methylene cyclic carbonates from propargylic alcohols and CO2 . New catalytic systems for the carboxylative cyclization of propargylic alcohols with CO2 . The challenges in the synthesis of cyclic carbonates via carboxylative cycloaddition of CO2 into propargylic alcohols. Mechanisms involved in the cycloaddition of CO2 with propargylic alcohols. Abstract: Transformation of carbon dioxide (CO2 ) into value-added organic compounds is a very important and hot research topic in green and sustainable chemistry because this greenhouse gas is a plentiful, nontoxic, nonflammable and renewable C1 feedstock. Among the various CO2 fixation reactions, carboxylative cycloaddition of CO2 into propargylic alcohols represents one of the most beautiful and attractive research topics in the field, since it offers the possibility for the fabrication of synthetically and biologically important five-membered cyclic carbonates from the simple and easily accessible starting materials in one step with 100 % atom economy. This review aims to give a comprehensive overview of the titled CO2 -fixation reactions, with particular emphasis on the mechanistic features of the reactions. The metal-catalyzed transformations are covered first. This is followed by ionic liquid and organocatalyzed reactions. Finally, the only reported example for electrochemically catalyzed reactions will be discussed at the end of this review.